Giving cancer patients the support they need - Nature Research (16552612) (2016)
A study that involved 129 female cancer patients above the age of 18 in Qatar found that the majority (88%) perceived psychosocial support as an important aspect of treatment. The respondents rated family support (92%) followed by religious support and support groups (86% each) as the most important support categories in their views. According to Qatar’s 2010 census, only 1.7% of its population are over the age of 60. This percentage is expected to increase ten-fold by 2050, which could have significant implications for cancer care. Cancers account for 18% of total deaths in Qatar. This high percentage is thought to be due to misconceptions about the disease that act as social and practical barriers to early screening. In fact, Qatar has a higher breast cancer mortality rate than other larger Arab states such as Saudi Arabia and the United Arab Emirates. A team of researchers in Qatar and the UK surveyed 129 female patients undergoing cancer treatment at Doha’s National Center for Cancer Care and Research to determine the level of importance they give to psychosocial support as part of their care strategy. Breast cancer was the most common diagnosis (63.6%) among the respondents. The majority (59.7%) identified as Muslim followed by 37.2% identifying as Christian. Most respondents (88.4%) perceived psychosocial support as being an important aspect of care. Four support categories were included in the questionnaire: family support, religious support, support groups and physician-referred support. Muslim and Arab patients together with those diagnosed with breast cancer deemed religious support as the most important in their view. Christian and non-Arab patients together with those diagnosed with other types of cancer favoured support groups as the most important category. Sixty-seven per cent of the respondents indicated that they would like to receive psychosocial support. Twenty-six per cent did not show a preference for any particular type, but 20% preferred receiving religious support, another 20% preferred receiving physician-referred support, and 13% indicated they would like to receive all four forms of support. Further research is still required with the aim of improving cancer patient care in Qatar, as “this research serves as only a glimpse into this multifaceted area of patient care…,” the researchers write in their study published in the Qatar Medical Journal. For example, future research could investigate the engagement of families in patient support and examine the potential of including religious support as part of their care, they say. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0